10. KNOWLEDGE AND PRACTICE ON DENGUE HEMORRHAGIC FEVER PREVENTION ON CAREGIVERS OF CHILDREN UNDER TREATMENT AT DEPARTMENT OF INFECTIOUS DISEASES - CHILDREN'S HOSPITAL 2, FROM 2024 TO 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of knowledge and practices of Dengue fever prevention among caregivers of children treated at the Department of Infectious Diseases - Children's Hospital 2, period 2024 - 2025.Methods: A cross-sectional descriptive study.Results: In total of 355 case research on caregivers of children treated at the Department of Infectious Diseases - Children's Hospital 2 in the period of 2024 - 2025, it was recorded: the mean age of the study subjects was 37.52 ± 8.07.  The ratio of caregivers of childrens with correct general knowledge on Dengue fever control was 50.1%; The ratio of caregivers of children with correct general practice on Dengue fever control was 32.1%, the study found a relationship between correct general knowledge and correct general practice  about Dengue prevention and control with p=0.007.Conclusion:  The ratio of caregivers of children treated at the Infection Department - Children's Hospital 2 in the period of 2024 - 2025 with correct knowledge about Dengue Hemorrhagic Fever prevention is average, the rate of correct practice on Dengue Hemorrhagic Fever prevention is still very low. It is necessary to strengthen health education communication work in the community as well as regularly repeat communication sessions at the Infection Department of Children's Hospital 2 to improve knowledge and pratices about Dengue hemorrhagic fever prevention and control.
Keywords: Dengue fever, mother, knowledge, practices, Children’s Hospital 2.